Short Communication: Antibacterial potential of Actinomycetes isolated from mangrove sediment in Tanjung Api-Api, South Sumatra, Indonesia - ROZIRWAN Rozirwan; Hebbri Iskandar Muda; Tengku Zia Ulqodry (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rozirwan, Muda HI, Ulqodry TZ. 2020. Short Communication: Antibacterial potential of Actinomycetes isolated from mangrove sediment in Tanjung Api-Api, South Sumatra, Indonesia. Biodiversitas 21: 5723-5728. Actinomycetes play an important role in the decomposition process of organic matter in mangrove sediments. This study was carried out to identify and evaluate the antagonistic activity of actinomycetes from mangrove sediment against Escherichia coli and Staphylococcus aureus. Identification of actinomycetes was performed based on morphological dan physiological characters. The antagonistic test was carried out against Escherichia coli and Staphylococcus aureus. A total of ten isolates had been successfully isolated and grouped into eight genera, including; Oerskovia H1, Micrococcus H2, Nocardia H3, Sporichtya H5, Corynebacterium H6, Jonesia H7, Actinomyces H10, and Streptomyces H8, H11, H12. Actinomycetes from mangrove sediment were gram-positive bacillus. The shape of the colony varied from circular to filamentous and irregular, with medium and large colony sizes. The colony appears white or yellow. The surface is convex and flat, aerobes and facultative anaerobes; capable of fermenting glucose. Five isolates have very strong growth inhibition activity against E. coli: Nocardia H3 (27.81mm ± 1.39), Actinomycetes H10 (27.75mm ± 2.48), Corynebacterium H6 (27.69mm ± 2.39), Micrococcus H2 (18.55mm ± 2.44), and Streptomyces H8 (17.92mm ± 2.70) while Streptomyces H8 (24.83mm ± 2.08), and Actinomycetes H10 (16.06mm ± 2.49) were active against S. aureus.